Staff Assessment Person-Directed Care Questionnaire: Adaptation and Validation for the Portuguese Population - Barbosa, Maria M. (2022)
Person-centered care aims to increase and guarantee the quality of care at residential care facilities for older adults. The implementation and development of this approach requires validated assessment tools, which are still lacking in Portugal. This study aims to adapt and validate for the Portuguese population the internationally and widely used essential instrument that is the Staff Assessment Person-Directed Care (SAPDC). The adaptation of the SAPDC included its translation, back translation, and a pilot-study. For validation, staff members were recruited by distributing the study via email and on social media. Respondents included 546 native Portuguese-speaking staff members working at residential care facilities for over 6 months. The mean score of SAPDC was 165.74 (SD = 36.78). The exploratory factor analysis showed eight conceptually distinct dimensions, considered adequate by the expert team. The total scale showed a very good internal consistency (α = .96) and excellent temporal stability assessed by Intraclass Correlation Coefficient (> .90). Providing a Portuguese version of the SAPDC is useful to substantiate technical and scientific advancements and define policies with implications on evolving care approaches. This tool helps optimize the quality and dignification of gerontological practices, which is urgent at Portuguese residential care facilities.